Analysis of phragmoplast kinetics during plant cytokinesis - Livanos, Pantelis; Chugh, Mayank; Müller, Sabine (Plant Protein Secretion, 2017)
In plants, the partitioning of daughter cells during cytokinesis is achieved via physical insertion of a membranous cell plate within the dividing parent cell. It is a cellular process of extensive protein secretion and membrane trafficking toward the plane of cell division and the cytoskeleton is an important facilitator of this process. A specialized cytoskeletal array termed phragmoplast expands centrifugally throughout cytokinesis and directs, mostly Golgi-derived vesicles that ultimately fuse to form the developing cell plate. The function of the phragmoplast in guiding cell plate synthesis has strongly motivated many scientists to monitor its dynamic behavior. In this chapter, we present an overview of basic principles and methods concerning the live imaging of cytokinetic plant cells using confocal laser scanning microscopy (CLSM) and the analysis of phragmoplast expansion.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Arabidopsis; Cell plate; CLSM; Cytokinesis; FM4-64; GFP; MAP4; MBD; Microtubules; Phragmoplast

Arabidopsis pavement cell shape formation involves spatially confined ROPGAP regulators - Lauster, Theresa; Stöckle, Dorothee; Gabor, Katharina; Haller, Theresa; Krieger, Natalie; Lotz, Pia; Mayakrishnan, Ravikumar; Späth, Ellen; Zimmermann, Steffi; Livanos, Pantelis; Müller, Sabine (Current Biology, 2022)
In many plant species, pavement cell development relies on the coordinated formation of interdigitating lobes and indentations. Polarity signaling via the activity of antagonistic Rho-related GTPases from plants (ROPs) was implicated in pavement cell development, but the spatiotemporal regulation remained unclear. Here, we report on the role of the PLECKSTRIN HOMOLOGY GTPase ACTIVATING PROTEINS (PHGAPS) during multipolar growth in pavement cell shape establishment. Loss of function in phgap1phgap2 double mutants severely affected the shape of Arabidopsis leaf epidermal pavement cells. Predominantly, PHGAPs interacted with ROP2 and displayed a distinct and microtubule-dependent enrichment along the anticlinal cell face and transfacial boundary of pavement cell indentation regions. This localization was established upon undulation initiation and was maintained throughout the expansion of the cell. Our data suggest that PHGAP1/REN2 and PHGAP2/REN3 are key players in the establishment of ROP2 activity gradients and underscore the importance of locally controlled ROP activity for the orchestrated establishment of multipolarity in epidermal cells.<br
Keywords: PHGAP; GTPase activating protein; Rho-related GTPases from plants; ROP; cell polarity signaling; microtubule; cytoskeleton; morphogenesis; pavement cell; cell shape

Arabidopsis TANGLED Identifies the Division Plane throughout Mitosis and Cytokinesis - Walker, Keely L.; Müller, Sabine; Moss, Dorianne; Ehrhardt, David W.; Smith, Laurie G. (Current Biology, 2007)
Background: In premitotic plant cells, the future division plane is predicted by a cortical ring of microtubules and F-actin called the preprophase band (PPB). The PPB persists throughout prophase, but is disassembled upon nuclear-envelope breakdown as the mitotic spindle forms. Following nuclear division, a cytokinetic phragmoplast forms between the daughter nuclei and expands laterally to attach the new cell wall at the former PPB site. A variety of observations suggest that expanding phragmoplasts are actively guided to the former PPB site, but little is known about how plant cells "remember" this site after PPB disassembly. Results: In premitotic plant cells, Arabidopsis TANGLED fused to YFP (AtTAN::YFP) colocalizes at the future division plane with PPBs. Strikingly, cortical AtTAN::YFP rings persist after PPB disassembly, marking the division plane throughout mitosis and cytokinesis. The AtTAN::YFP ring is relatively broad during preprophase/prophase and mitosis; narrows to become a sharper, more punctate ring during cytokinesis; and then rapidly disassembles upon completion of cytokinesis. The initial recruitment of AtTAN::YFP to the division plane requires microtubules and the kinesins POK1 and POK2, but subsequent maintenance of AtTAN::YFP rings appears to be microtubule independent. Consistent with the localization data, analysis of Arabidopsis tan mutants shows that AtTAN plays a role in guidance of expanding phragmoplasts to the former PPB site. Conclusions: AtTAN is implicated as a component of a cortical guidance cue that remains behind when the PPB is disassembled and directs the expanding phragmoplast to the former PPB site during cytokinesis. © 2007 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: CELLBIO; CELLCYCLE

Assessment of Spindle Shape Control by Spindle Poleward Flux Measurements and FRAP Bulk Analysis - Müller, Sabine (Methods in Molecular Biology, 2023)
In plants, the segregation of genetic material is achieved by an acentrosomal, mitotic spindle. This macromolecular machinery consists of different microtubule subpopulations and interacting proteins. The majority of what we know about the assembly and shape control of the mitotic spindle arose from vertebrate model systems. The dynamic properties of the individual tubulin polymers are crucial for the accurate assembly of the spindle array and are modulated by microtubule-associated motor and non-motor proteins. The mitotic spindle relies on a phenomenon called poleward microtubule flux that is critical to establish spindle shape, chromosome alignment, and segregation. This flux is under control of the non-motor microtubule-associated proteins and force-generating motors. Despite the large number of (plant-specific) kinesin motor proteins expressed during mitosis, their mitotic roles remain largely elusive. Moreover, reports on mitotic spindle formation and shape control in higher plants are scarce. In this chapter, an overview of the basic principles and methods concerning live imaging of prometa- and metaphase spindles and the analysis of spindle microtubule flux using fluorescence recovery after photobleaching is provided.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Arabidopsis; Cell division; CLSM; Fluorescence recovery after photobleaching; Kymograph; Microtubule dynamics; Poleward flux; Spindle

Cloning and expression of cDNAs encoding α1,3-fucosyltransferase homologues from Arabidopsis thaliana - Wilson, Iain B.H.; Rendić, Dubravko; Freilinger, Angelika; Dumić, Jerka; Altmann, Friedrich; Mucha, Jan; Müller, Sabine; Hauser, Marie-Theres (Biochimica et Biophysica Acta - General Subjects, 2001)
The core α1,3-fucosyltransferases are involved in the synthesis of glycans specific to plants and invertebrates which are known to be immunogenic and allergenic. We report the identification, isolation and characterisation of the cDNAs of three genes (FucTA, FucTB and FucTC) encoding proteins similar to α1,3-fucosyltransferases in Arabidopsis thaliana. Reverse transcription-polymerase chain reaction was used to amplify the full length coding sequence of FucTA. The FucTA gene, which consists of seven exons, encodes a presumptive protein of 501 amino acids showing an overall sequence identity of 66% to the protein encoded by the recently isolated mung bean Fuc-T C3 cDNA. FucTA was expressed in Pichia pastoris under the control of the AOX1 gene promoter. The soluble enzyme was found to catalyse the same reaction as mung bean core α1,3-fucosyltransferase as judged by analyses of the products by MALDI-TOF and high-performance liquid chromatography. The FucTB cDNA was isolated from a λ-ZAP library, but the clone used an alternative splicing site between the second and third exon resulting in a premature stop codon. The FucTC gene encodes a protein with less than 40% identity to FucTA across 115 amino acids of a total of 401 amino acids and is a member of a new sub-family of plant α1,3/4-fucosyltransferase homologues. © 2001 Elsevier Science B.V.
Created from Fastlane, Scopus look-up
Keywords: Arabidopsis; Fucosyltransferase

Division plane control in plants: new players in the band - Müller, Sabine; Wright, Amanda J.; Smith, Laurie G. (Trends in Cell Biology, 2009)
Unique mechanisms are used to orient cell division planes in plants. A cortical ring of cytoskeletal filaments called the preprophase band (PPB) predicts the future division plane during G2 and is disassembled as the mitotic spindle forms, leaving behind a 'cortical division site' (CDS) that guides the placement of the new cell wall (cell plate) during cytokinesis. The molecular features of the CDS have remained elusive for decades. Recently, a few proteins have at last been identified that are specifically localized to or excluded from the CDS and that participate in the orientation, attachment or maturation of cell plates. Recent progress has also been made in identifying proteins needed for PPB formation and thus for division plane establishment. © 2009 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-07-01

Division Plane Establishment and Cytokinesis - Livanos, Pantelis; Müller, Sabine; Müller, Sabine (Annual Review of Plant Biology, 2019)
Plant cells divide their cytoplasmic content by forming a new membrane compartment, the cell plate, via a rerouting of the secretory pathway toward the division plane aided by a dynamic cytoskeletal apparatus known as the phragmoplast. The phragmoplast expands centrifugally and directs the cell plate to the preselected division site at the plasma membrane to fuse with the parental wall. The division site is transiently decorated by the cytoskeletal preprophase band in preprophase and prophase, whereas a number of proteins discovered over the last decade reside continuously at the division site and provide a lasting spatial reference for phragmoplast guidance. Recent studies of membrane fusion at the cell plate have revealed the contribution of functionally conserved eukaryotic proteins to distinct stages of cell plate biogenesis and emphasize the coupling of cell plate formation with phragmoplast expansion. Together with novel findings concerning preprophase band function and the setup of the division site, cytokinesis and its spatial control remain an open-ended field with outstanding and challenging questions to resolve.
CRIS-Team Scopus Importer:2021-07-01
Keywords: cell plate; cytokinesis; cytoskeleton; division plane; phragmoplast; preprophase band

Dual localized kinesin-12 POK2 plays multiple roles during cell division and interacts with MAP65-3 - Herrmann, Arvid; Livanos, Pantelis; Lipka, Elisabeth; Gadeyne, Astrid; Hauser, Marie-Theres; Van Damme, Daniel; Müller, Sabine (EMBO Reports, 2018)
Kinesins are versatile nano-machines that utilize variable non-motor domains to tune specific motor microtubule encounters. During plant cytokinesis, the kinesin-12 orthologs, PHRAGMOPLAST ORIENTING KINESIN (POK)1 and POK2, are essential for rapid centrifugal expansion of the cytokinetic apparatus, the phragmoplast, toward a pre-selected cell plate fusion site at the cell cortex. Here, we report on the spatio-temporal localization pattern of POK2, mediated by distinct protein domains. Functional dissection of POK2 domains revealed the association of POK2 with the site of the future cell division plane and with the phragmoplast during cytokinesis. Accumulation of POK2 at the phragmoplast midzone depends on its functional POK2 motor domain and is fine-tuned by its carboxy-terminal region that also directs POK2 to the division site. Furthermore, POK2 likely stabilizes the phragmoplast midzone via interaction with the conserved microtubule-associated protein MAP65-3/PLEIADE, a well-established microtubule cross-linker. Collectively, our results suggest that dual localized POK2 plays multiple roles during plant cell division.
CRIS-Team Scopus Importer:2021-07-01
Keywords: cytokinesis; cytoskeleton; division plane; phragmoplast; preprophase band

Evaluation of a home-made SYBR® Green I reaction mixture for real-time PCR quantification of gene expression - Karsai, Albert; Müller, Sabine; Platz, Stefan; Hauser, Marie-Theres (Biotechniques, 2002)
Real-time PCR is an accurate method that can be used for the quantification of specific DNA molecules. Here we provide a protocol for SYBR® Green I in real-time PCR applications using plastic reaction tubes. We report that SYBR Green I is alkali labile and once degraded inhibits the PCR. In our optimized protocol, diluted aliquots of SYBR Green I remain stable for at least two weeks. We also evaluated different cDNA synthesis protocols for the quantification of multiple genes from the same cDNA preparation. The best result was obtained with cDNAs synthesized by OmniScript™ reverse transcriptase from 2.5 μg total RNA using oligo d(T)18 primers. The cDNA reactions could be diluted 1:25, allowing the quantification of up to 125 different medium expressed genes of Arabidopsis. Extension times ranged between 20 and 40 bp/s for accurate quantification of PCR products up to approximately 400 bp in the Rotor-Gene 2000 system. Using our optimized real-time PCR protocol, the reproducibility and amplification efficiency was high and comparable to a commercially available SYBR Green 1 kit. Furthermore, the sensitivity allowed us to quantify 10-20 copies of mRNA and dsDNA. Thus, the protocol eliminates the need for expensive pre-made kits.
Created from Fastlane, Scopus look-up

Guidelines for naming and studying plasma membrane domains in plants - Jaillais, Yvon; Bayer, Emmanuelle; Bergmann, Dominique C.; Botella, Miguel A.; Boutté, Yohann; Bozkurt, Tolga O.; Caillaud, Marie Cecile; Germain, Véronique; Grossmann, Guido; Heilmann, Ingo; Hemsley, Piers A.; Kirchhelle, Charlotte; et al. (Nature Plants, 2024)
Biological membranes play a crucial role in actively hosting, modulating and coordinating a wide range of molecular events essential for cellular function. Membranes are organized into diverse domains giving rise to dynamic molecular patchworks. However, the very definition of membrane domains has been the subject of continuous debate. For example, in the plant field, membrane domains are often referred to as nanodomains, nanoclusters, microdomains, lipid rafts, membrane rafts, signalling platforms, foci or liquid-ordered membranes without any clear rationale. In the context of plant–microbe interactions, microdomains have sometimes been used to refer to the large area at the plant–microbe interface. Some of these terms have partially overlapping meanings at best, but they are often used interchangeably in the literature. This situation generates much confusion and limits conceptual progress. There is thus an urgent need for us as a scientific community to resolve these semantic and conceptual controversies by defining an unambiguous nomenclature of membrane domains. In this Review, experts in the field get together to provide explicit definitions of plasma membrane domains in plant systems and experimental guidelines for their study. We propose that plasma membrane domains should not be considered on the basis of their size alone but rather according to the biological system being considered, such as the local membrane environment or the entire cell.
CRIS-Team Scopus Importer:2024-08-23

Identification of cytoskeleton-associated genes expressed during Arabidopsis syncytial endosperm development - Day, Robert C.; Mueller, Sabine; Macknight, Richard C. (Plant Signaling & Behavior, 2009)
During the early stages of Arabidopsis seed development, the endosperm is syncytial and proliferates rapidly through multiple rounds of mitosis in the absence of cytokinesis and cell wall formation. This stage of endosperm development is important in determining seed viability and size. To identify genes involved in syncytial endosperm development, we analyzed the endosperm transcriptome, obtained using laser capture microdissection of developing seeds at four days after pollination. Our results support the idea that similar sets of genes are required for conventional somatic mitosis with cytokinesis and syncytial proliferation. Furthermore, we identify cytoskeleton associated genes that may act to facilitate syncytial development thereby providing an important resource for further characterization of the processes involved in syncytial endosperm development. © 2009 Landes Bioscience.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Arabidopsis; Cytoskeleton; Endosperm; Seed; Syncytium; Transcriptome

IQ67 DOMAIN proteins facilitate preprophase band formation and division-plane orientation - Kumari, Pratibha; Dahiya, Pradeep; Livanos, Pantelis; Zergiebel, Luise; Koelling, Malte; Poeschl, Yvonne; Stamm, Gina; Hermann, Arvid; Abel, Steffen; Buerstenbinder, Katharina; Müller, Sabine (Nature Plants, 2021)
Spatiotemporal control of cell division is essential for the growth and development of multicellular organisms. In plant cells, proper cell plate insertion during cytokinesis relies on the premitotic establishment of the division plane at the cell cortex. Two plant-specific cytoskeleton arrays, the preprophase band (PPB) and the phragmoplast, play important roles in division-plane orientation and cell plate formation, respectively1. Microtubule organization and dynamics and their communication with membranes at the cortex and cell plate are coordinated by multiple, mostly distinct microtubule-associated proteins2. How division-plane selection and establishment are linked, however, is still unknown. Here, we report members of the Arabidopsis IQ67 DOMAIN (IQD) family3 as microtubule-targeted proteins that localize to the PPB and phragmoplast and additionally reside at the cell plate and a polarized cortical region including the cortical division zone (CDZ). IQDs physically interact with PHRAGMOPLAST ORIENTING KINESIN (POK) proteins4,5 and PLECKSTRIN HOMOLOGY GTPase ACTIVATING (PHGAP) proteins6, which are core components of the CDZ1. The loss of IQD function impairs PPB formation and affects CDZ recruitment of POKs and PHGAPs, resulting in division-plane positioning defects. We propose that IQDs act as cellular scaffolds that facilitate PPB formation and CDZ set-up during symmetric cell division.
CRIS-Team Scopus Importer:2021-07-01

KINESIN-12E regulates metaphase spindle flux and helps control spindle size in Arabidopsis - Herrmann, Arvid; Livanos, Pantelis; Zimmermann, Steffi; Berendzen, Kenneth; Rohr, Leander; Lipka, Elisabeth; Müller, Sabine (The Plant Cell, 2021)
The bipolar mitotic spindle is a highly conserved structure among eukaryotes that mediates chromosome alignment and segregation. Spindle assembly and size control are facilitated by force-generating microtubule-dependent motor proteins known as kinesins. In animals, kinesin-12 cooperates with kinesin-5 to produce outward-directed forces necessary for spindle assembly. In plants, the relevant molecular mechanisms for spindle formation are poorly defined. While an Arabidopsis thaliana kinesin-5 ortholog has been identified, the kinesin-12 ortholog in plants remains elusive. In this study, we provide experimental evidence for the function of Arabidopsis KINESIN-12E in spindle assembly. In kinesin-12e mutants, a delay in spindle assembly is accompanied by the reduction of spindle size, demonstrating that KINESIN-12E contributes to mitotic spindle architecture. Kinesin-12E localization is mitosis-stage specific, beginning with its perinuclear accumulation during prophase. Upon nuclear envelope breakdown, KINESIN-12E decorates subpopulations of microtubules in the spindle and becomes progressively enriched in the spindle midzone. Furthermore, during cytokinesis, KINESIN-12E shares its localization at the phragmoplast midzone with several functionally diversified Arabidopsis KINESIN-12 members. Changes in the kinetochore and in prophase and metaphase spindle dynamics occur in the absence of KINESIN-12E, suggest it might play an evolutionarily conserved role during spindle formation similar to its spindle-localized animal kinesin-12 orthologs.
CRIS-Team Scopus Importer:2021-07-01

Linking Separase to Microtubule Dynamics - Müller, Sabine (Developmental Cell, 2016)
The Arabidopsis separase homolog, AtESP, associates with microtubules and affects cell polarity but does not bind microtubules directly. In this issue of Developmental Cell, Moschou et al. (2016) show that AtESP teams up with the CENP-E kinesin Kin7 to promote microtubule stabilization, an activity independent of separase proteolytic activity.
CRIS-Team Scopus Importer:2021-07-01

Mechanisms of plant cell division - Müller, Sabine; et al. (Wiley Interdisciplinary Reviews: Developmental Biology, 2015)
Plant cells are confined by a network of cellulosic walls that imposes rigid control over the selection of division plane orientations, crucial for morphogenesis and genetically regulated. While in animal cells and yeast, the actin cytoskeleton is instrumental in the execution of cytokinesis, in plant cells the microtubule cytoskeleton is taking the lead in spatially controlling and executing cytokinesis by the formation of two unique, plant-specific arrays, the preprophase band (PPB) and the phragmoplast. The formation of microtubule arrays in plant cells is contingent on acentrosomal microtubule nucleation. At the onset of mitosis, the PPB defines the plane of cell division where the partitioning cell wall is later constructed by the cytokinetic phragmoplast, imposing a spatio-temporal relationship between the two processes. Current research progress in the field of plant cell division focuses on identifying and tying the links between early and late events in spatial control of cytokinesis and how microtubule array formation is regulated in plant cells. (C) 2015 Wiley Periodicals, Inc.

Nitrosative stress triggers microtubule reorganization in Arabidopsis thaliana - Lipka, Elisabeth; Müller, Sabine (Journal of Experimental Botany, 2014)
Microtubules (MTs) are essential components of the cytoskeleton and fulfil multiple cellular functions in developmental processes, readily responding to intrinsic and external cues. Nitric oxide signalling is well established in plants, and the MT cytoskeleton is one of its potential targets. To mimic low level nitrosative stress, growth medium was supplemented with 3-nitro-l-tyrosine (NO2-Tyr), a nitrated form of the amino acid tyrosine, and concentration-dependent changes in root growth rate and a reduction in cell division frequencies in Arabidopsis thaliana were observed. In addition, it is reported that exposure to low NO2-Tyr concentrations was not detrimental to plant health and caused subtle and reversible defects. In contrast, growth defects caused by high NO2-Tyr concentrations could not be reversed. Live cell imaging of an MT reporter line revealed that treatment with a low concentration of NO2-Tyr correlated with disorganized cortical MT arrays and associated non-polar cell expansion in the elongation zone. NO2-Tyr treatment antagonized the effects of taxol and oryzalin, further supporting the association of NO2-Tyr with MTs. Furthermore, oblique division plane orientations were observed which were probably induced prior to cytokinesis. © 2014 The Author.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Cytoskeleton dynamics; microtubule; nitrosative stress; phragmoplast

Nonradioactive labeling of large DNA fragments for genome walking, RFLP and northern blot analysis - Adhami, Farzaneh; Müller, Sabine; Hauser, Marie-Theres (Biotechniques, 1999)
In this report, we present a simple nonradioactive labeling procedure for DNA fragments of high specific labeling density that can be used for a variety of applications. The protocol is based on the universal mono- functional platinium reagent for chemical digoxigenin (DIG) labeling of nucleic acids. The labeling protocol was optimized for large DNA templates as complete bacterial artificial chromosomes (BAC). Variations of incubation time and temperature improved the labeling density such that about 30% of the nucleotides were DIG-modified within 30 min. Furthermore, the refined procedure generates in a single-tube reaction and without prior digestion- labeled DNA fragments of 0.5-4.0 kb from a 130-kb template. Hybridization experiments were performed on Southern and northern blots and allowed the detection of single copy genes in 2.5 μg genomic DNA from Arabidopsis thaliana, which has a haploid genome size of 0.13 pg (ca. 120 Mb) and medium expressed transcripts from 0.8 μg poly(A)+ RNA, respectively. The extremely high specific labeling density, the stability and the universal application of the probe generated with the platinium reagent makes this method a useful alternative to classical radioactive nuclei acids labeling techniques.
Created from Fastlane, Scopus look-up

On the edge — how plant cells monitor growth - Kriechbaum, Choy; Müller, Sabine (Nature Plants, 2024)
Cell edges are part of a coordinate system used by the cell to direct three-dimensional growth in an organized manner. They emerge as signalling hubs with unique composition, capable of sensing mechanical stresses derived from neighbouring cells, to negotiate and harmonize individual cellular growth rates, therefore avoiding mechanical conflict.
CRIS-Team Scopus Importer:2024-03-15

Phragmoplast Orienting Kinesin 2 Is a Weak Motor Switching between Processive and Diffusive Modes - Chugh, Mayank; Reissner, Maja; Bugiel, Michael; Lipka, Elisabeth; Herrmann, Arvid; Roy, Basudev; Müller, Sabine; Schaeffer, Erik (Biophysical Journal, 2018)
Plant development and morphology relies on the accurate insertion of new cell walls during cytokinesis. However, how a plant cell correctly orients a new wall is poorly understood. Two kinesin class-12 members, phragmoplast orienting kinesin 1 (POK1) and POK2, are involved in the process, but how these molecular machines work is not known. Here, we used in vivo and single-molecule in vitro measurements to determine how Arabidopsis thaliana POK2 motors function mechanically. We found that POK2 is a very weak, on average plus-end-directed, moderately fast kinesin. Interestingly, POK2 switches between processive and diffusive modes characterized by an exclusive-state mean-squared-displacement analysis. Our results support a model that POK motors push against peripheral microtubules of the phragmoplast for its guidance. This pushing model may mechanically explain the conspicuous narrowing of the division site. Together, our findings provide mechanical insight into how active motors accurately position new cell walls in plants.
CRIS-Team Scopus Importer:2021-07-01

Plant Cell Division - Müller, Sabine (2012)
Cell division is characterised by the segregation of genetic material and the redistribution of cellular contents facilitated by the cytoskeleton. Plant cells derive from divisions in the meristems of developing organs. However, plant cells are enclosed in rigid cell walls, unable to migrate and change their location within tissues. Thus, positions of division planes, together with successive polarised cell expansion are the major determinants of cell shape and consequently morphology of plants. The basic building blocks of the cytoskeleton, tubulins, actins and cytoskeleton associated motor- and nonmotor-proteins are conserved. Yet, plants have developed unique cytoskeletal arrays and molecular mechanism to determine the division plane very early in mitosis and to facilitate the synthesis and insertion of the partitioning cell plate at the end of cell division.

Plant cell division — defining and finding the sweet spot for cell plate insertion - Müller, Sabine (Current Opinion in Cell Biology, 2019)
The plant microtubules form unique arrays using acentrosomal microtubule nucleation pathways, yet utilizing evolutionary conserved centrosomal proteins. In cytokinesis, a multi-component cytoskeletal apparatus, the phragmoplast mediates the biosynthesis of the new cell plate by dynamic centrifugal expansion, a process that demands exquisite coordination of microtubule turnover and endomembrane trafficking. At the same time, the phragmoplast is guided to meet with the parental wall at a cortical site that is predefined before mitotic entry and transiently marked by the preprophase band of microtubules. The cortical division zone maintains positional information of the selected division plane for the entire duration of cell division and for the guidance of the phragmoplast during cytokinesis. Its establishment is an essential requirement for normal plant organogenesis, due to the confinement of cells by rigid cell walls.
CRIS-Team Scopus Importer:2021-07-01

Plant cytokinesis-No ring, No constriction but centrifugal construction of the partitioning membrane - Müller, Sabine; Juergens, Gerd (Seminars in Cell & Developmental Biology, 2016)
Plants have evolved a unique way of partitioning the cytoplasm of dividing cells: Instead of forming a contractile ring that constricts the plasma membrane, plant cells target membrane vesicles to the plane of division where the vesicles fuse with one another to form the partitioning membrane. Plant cytokinesis starts in the centre and progresses towards the periphery, culminating in the fusion of the partitioning membrane with the parental plasma membrane. This membrane dynamics is orchestrated by a specific cytoskeletal array named phragmoplast that originates from interzone spindle remnants. Here we review the properties of the process as well as molecules that play specific roles in that process.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Cell plate; Kinesin; Membrane fusion; Phragmoplast; Preprophase band; SNARE

Plant Cytokinesis: Terminology for Structures and Processes - Smertenko, Andrei; Assaad, Farhah; Baluska, Frantisek; Bezanilla, Magdalena; Buschmann, Henrik; Drakakaki, Georgia; Hauser, Marie-Theres; Janson, Marcel; Mineyuki, Yoshinobu; Moore, Ian; Müller, Sabine; Murata, Takashi; et al. (Trends in Cell Biology, 2017)
Plant cytokinesis is orchestrated by a specialized structure, the phragmoplast. The phragmoplast first occurred in representatives of Charophyte algae and then became the main division apparatus in land plants. Major cellular activities, including cytoskeletal dynamics, vesicle trafficking, membrane assembly, and cell wall biosynthesis, cooperate in the phragmoplast under the guidance of a complex signaling network. Furthermore, the phragmoplast combines plant-specific features with the conserved cytokinetic processes of animals, fungi, and protists. As such, the phragmoplast represents a useful system for understanding both plant cell dynamics and the evolution of cytokinesis. We recognize that future research and knowledge transfer into other fields would benefit from standardized terminology. Here, we propose such a lexicon of terminology for specific structures and processes associated with plant cytokinesis. A large number of phragmoplast proteins have been identified. Electron microscopy/tomography studies have produced nanoscale information about the architecture of phragmoplast and cell plate assembly stages in cryofixed cells. Novel components of the cortical division zone and cell plate fusion site have been discovered. This information lays a foundation for understanding how plant cells memorize the division plane throughout mitosis and how the cell plate is guided to its predetermined attachment site. MAP65 and plus end-directed kinesins contribute to the maintenance of the antiparallel overlap of phragmoplast microtubules. In addition, the MAP65–TRAPPII interaction plays a key role in cell plate assembly. Actin filaments align parallel to microtubules in the phragmoplast, while some microfilaments extend from cell plate margin to guide its expansion towards the fusion site.
CRIS-Team Scopus Importer:2021-07-01
Keywords: cell plate; cytokinesis; division plane; phragmoplast; preprophase band

Plant Intracellular Transport: Tracing Functions of the Retrograde Kinesin - Müller, Sabine (Current Biology, 2015)
Summary Adding to its varied repertoire of functions in cell morphogenesis and cell division, a molecular motor protein of the kinesin-14 class has recently been implicated in rapid retrograde transport along cellular tracks in moss.
CRIS-Team Scopus Importer:2021-07-01

Plant kinesin-12: Localization heterogeneity and functional implications - Livanos, Pantelis; Müller, Sabine (International Journal of Molecular Sciences, 2019)
Kinesin-12 family members are characterized by an N-terminal motor domain and the extensive presence of coiled-coil domains. Animal orthologs display microtubule plus-end directed motility, bundling of parallel and antiparallel microtubules, plus-end stabilization, and they play a crucial role in spindle assembly. In plants, kinesin-12 members mediate a number of developmental processes including male gametophyte, embryo, seedling, and seed development. At the cellular level, they participate in critical events during cell division. Several kinesin-12 members localize to the phragmoplast midzone, interact with isoforms of the conserved microtubule cross-linker MICROTUBULE-ASSOCIATED PROTEIN 65 (MAP65) family, and are required for phragmoplast stability and expansion, as well as for proper cell plate development. Throughout cell division, a subset of kinesin-12 reside, in addition or exclusively, at the cortical division zone and mediate the accurate guidance of the phragmoplast. This review aims to summarize the current knowledge on kinesin-12 in plants and shed some light onto the heterogeneous localization and domain architecture, which potentially conceals functional diversification.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Cytokinesis; Division plane determination; Gametogenesis; Microtubules; Phragmoplast midzone

Plasma membrane and cytoplasmic compartmentalization: A dynamic structural framework required for pollen tube tip growth - Fritz, Carolin; Reimann, Theresa; Adler, Jeremy; Knab, Johanna; Schulmeister, Sylwia; Kriechbaum, Choy; Müller, Sabine; Parmryd, Ingela; Kost, Benedikt (Plant Physiology, 2024)
Rapid, unidirectional pollen tube tip growth is essential for fertilization and widely employed as a model of polar cell expansion, a process crucial for plant morphogenesis. Different proteins and lipids with key functions in the control of polar cell expansion are associated with distinct domains of the plasma membrane (PM) at the pollen tube tip. These domains need to be dynamically maintained during tip growth, which depends on massive secretory and endocytic membrane trafficking. Very little is currently known about the molecular and cellular mechanisms responsible for the compartmentalization of the pollen tube PM. To provide a reliable structural framework for the further characterization of these mechanisms, an integrated quantitative map was compiled of the relative positions in normally growing Nicotiana tabacum (tobacco) pollen tubes of PM domains (i) enriched in key signaling proteins or lipids, (ii) displaying high membrane order, or (iii) in contact with cytoplasmic structures playing important roles in apical membrane trafficking. Previously identified secretory and endocytic PM domains were also included in this map. Internalization of regulatory proteins or lipids associated with PM regions overlapping with the lateral endocytic domain was assessed based on brefeldin A treatment. These analyses revealed remarkable aspects of the structural organization of tobacco pollen tube tips, which (i) enhance our understanding of cellular and regulatory processes underlying tip growth and (ii) highlight important areas of future research.
Created from Fastlane, Scopus look-up

Potential roles for kinesins at the cortical division site - Lipka, Elisabeth; Müller, Sabine (Frontiers in Plant Science, 2012)
Spatial control of cytokinesis is critical for cell and plant morphology. The plane of cell division is established at G2/M transition and is initially demarcated at the cortex of the cell by the cytoskeletal preprophase band (PPB) and subsequently throughout mitosis by the cortical division zone (CDZ). Few kinesins, belonging to different classes of the superfamily, either display a distinct spatio-temporal localization at the PPB and CDZ, or genetic evidence proposes a specific function there. Protein phosphorylation and degradation are likely directing the cell cycle-dependent localization and activity of some of these kinesins, as indicated by mutation of respective conserved motifs. Furthermore, kinesins are required for continuous recruitment of CDZ identity markers to the CDZ. This review summarizes the limited current knowledge of kinesins potentially involved in the steps required for correctly oriented division planes, considering localization patterns and genetic evidence, and discussing kinesin function in context with interaction partners and cell cycle regulation. © 2012 Lipka and Müller.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Cell division; Cortical division site; Kinesin; Phragmoplast; Preprophase band

Putative RopGAPs impact division plane selection and interact with kinesin-12 POK1 - Stoeckle, Dorothee; Herrmann, Arvid; Lipka, Elisabeth; Lauster, Theresa; Gavidia, Richard; Zimmermann, Steffi; Müller, Sabine (Nature Plants, 2016)
Cell shape is defined by the surrounding cell walls in plants. Thus, spatial control over cell division planes and cell expansion polarity are essential to maintain cell morphology. In eukaryotes, cell polarity and expansion are controlled by Rho GTPase signalling, regulating cytoskeletal reorganization and vesicle trafficking1. However, until now, Rho signalling was not implicated in mitotic events in plants. Here, we report a pair of putative Rho GTPase activating proteins (RhoGAPs) that interact with the mitosis-specific kinesin-12 POK1, a core component of the cortical division zone/site (CDZ/CDS) that is required for division plane maintenance in Arabidopsis 2-4. The designated pleckstrin homology GAPs (PHGAPs) are cytoplasmic and plasma membrane associated in interphase, but during mitosis they additionally localize to the CDZ/CDS in a POK-dependent manner. In contrast to pok1 pok2 mutants, phgap1 phgap2 double mutants show moderate cell wall positioning defects as a consequence of inaccurate positioning of the cortical division zone marker POK1. We conclude that loss of PHGAP function interferes with division plane selection in proliferative cell divisions.
CRIS-Team Scopus Importer:2021-07-01

RanGAP1 is a continuous marker of the Arabidopsis cell division plane - Xu, Xianfeng Morgan; Zhao, Qiao; Rodrigo-Peiris, Thushani; Brkljacic, Jelena; He, Chao Sylvia; Mueller, Sabine; Meier, Iris (Proceedings of the National Academy of Sciences of the United States of America, 2008)
In higher plants, the plane of cell division is faithfully predicted by the preprophase band (PPB). The PPB, a cortical ring of microtubules and F-actin, disassembles upon nuclear-envelope breakdown. During cytokinesis, the expanding cell plate fuses with the plasma membrane at the cortical division site, the site of the former PPB. The nature of the "molecular memory" that is left behind by the PPB and is proposed to guide the cell plate to the cortical division site is unknown. RanGAP is the GTPase activating protein of the small GTPase Ran, which provides spatial information for nucleocytoplasmic transport and various mitotic processes in animals. Here, we show that, in dividing root cells, Arabidopsis RanGAP1 concentrates at the PPB and remains associated with the cortical division site during mitosis and cytokinesis, requiring its N-terminal targeting domain. In a fass/ton2 mutant, which affects PPB formation, RanGAP1 recruitment to the PPB site is lost, while its PPB retention is microtubule-independent. RanGAP1 persistence at the cortical division site, but not its initial accumulation at the PPB requires the 2 cytokinesis-regulating kinesins POK1 and POK2. Depletion of RanGAP by inducible RNAi leads to oblique cell walls and cell-wall stubs in root cell files, consistent with cytokinesis defects. We propose that Arabidopsis RanGAP, a continuous positive protein marker of the plant division plane, has a role in spatial signaling during plant cell division. © 2008 by The National Academy of Sciences of the USA.
Created from Fastlane, Scopus look-up
Keywords: Cytokinesis; Nuclear pore; Preprophase band; Ran cycle

ROPGAP-dependent interaction between brassinosteroid and ROP2-GTPase signaling controls pavement cell shape in Arabidopsis - Zhang, Cheng; Lauster, Theresa; Tang, Wenxin; Houbaert, Anaxi; Zhu, Shanshuo; Eeckhout, Dominique; De Smet, Ive; De Jaeger, Geert; Jacobs, Thomas B.; Xu, Tongda; Müller, Sabine; Russinova, Eugenia (Current Biology, 2022)
The epidermal pavement cell shape in Arabidopsis is driven by chemical and mechanical cues that direct partitioning mechanisms required for the establishment of the lobe- and indentation-defining polar sites. Brassinosteroid (BR) hormones regulate pavement cell morphogenesis, but the underlying mechanism remains unclear. Here, we identified two PLECKSTRIN HOMOLOGY GTPase-ACTIVATING proteins (PHGAPs) as substrates of the GSK3-like kinase BR-INSENSITIVE2 (BIN2). The phgap1phgap2 mutant displayed severe epidermal cell shape phenotypes, and the PHGAPs were markedly enriched in the anticlinal face of the pavement cell indenting regions. BIN2 phosphorylation of PHGAPs was required for their stability and polarization. BIN2 inhibition activated ROP2-GTPase signaling specifically in the lobes because of PHGAP degradation, while the PHGAPs restrained ROP2 activity in the indentations. Hence, we connect BR and ROP2-GTPase signaling pathways via the regulation of PHGAPs and put forward the importance of spatiotemporal control of BR signaling for pavement cell interdigitation.<br
Keywords: Brassinosteroid hormones; BIN2; PHGAP; ROP2; phosphorylation; pavement cell shape

The microtubule-associated kinase-like protein RUNKEL functions in somatic and syncytial cytokinesis - Krupnova, Tamara; Stierhof, York-Dieter; Hiller, Ulrike; Strompen, Georg; Müller, Sabine (Plant Journal, 2013)
Summary The microtubule (MT)-associated putative kinase RUNKEL (RUK) is an important component of the phragmoplast machinery involved in cell plate formation in Arabidopsis somatic cytokinesis. Since loss-of-function ruk mutants display seedling lethality, it was previously not known whether RUK functions in mature sporophytes or during gametophyte development. In this study we utilized RUK proteins that lack the N-terminal kinase domain to further examine biological processes related to RUK function. Truncated RUK proteins when expressed in wild-type Arabidopsis plants cause cellularization defects not only in seedlings and adult tissues but also during male meiocyte development, resulting in abnormal pollen and reduced fertility. Ultrastructural analysis of male tetrads revealed irregular and incomplete or absent intersporal cell walls, caused by disorganized radial MT arrays. Moreover, in ruk mutants endosperm cellularization defects were also caused by disorganized radial MT arrays. Intriguingly, in seedlings expressing truncated RUK proteins, the kinesin HINKEL, which is required for the activation of a mitogen-activated protein kinase signaling pathway regulating phragmoplast expansion, was mislocalized. Together, these observations support a common role for RUK in both phragmoplast-based cytokinesis in somatic cells and syncytial cytokinesis in reproductive cells. © 2013 The Authors The Plant Journal © 2013 John Wiley & Sons Ltd.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Arabidopsis thaliana; cellularization; cytokinesis; gametogenesis; MAPK signaling; meiosis; microspore; microtubule; phragmoplast

The phragmoplast-orienting kinesin-12 class proteins translate the positional information of the preprophase band to establish the cortical division zone in Arabidopsis thaliana - Lipka, Elisabeth; Gadeyne, Astrid; Stoeckle, Dorothee; Zimmermann, Steffi; De Jaeger, Geert; Ehrhardt, David W.; Kirik, Viktor; Van Damme, Daniel; Müller, Sabine (The Plant Cell, 2014)
The preprophase band (PPB) is a faithful but transient predictor of the division plane in somatic cell divisions. Throughout mitosis the PPBs positional information is preserved by factors that continuously mark the division plane at the cell cortex, the cortical division zone, by their distinct spatio-temporal localization patterns. However, the mechanism maintaining these identity factors at the plasma membrane after PPB disassembly remains obscure. The pair of kinesin-12 class proteins PHRAGMOPLAST ORIENTING KINESIN1 (POK1) and POK2 are key players in division plane maintenance. Here, we show that POK1 is continuously present at the cell cortex, providing a spatial reference for the site formerly occupied by the PPB. Fluorescence recovery after photobleaching analysis combined with microtubule destabilization revealed dynamic microtubule-dependent recruitment of POK1 to the PPB during prophase, while POK1 retention at the cortical division zone in the absence of cortical microtubules appeared static. POK function is strictly required to maintain the division plane identity factor TANGLED (TAN) after PPB disassembly, although POK1 and TAN recruitment to the PPB occur independently during prophase. Together, our data suggest that POKs represent fundamental early anchoring components of the cortical division zone, translating and preserving the positional information of the PPB by maintaining downstream identity markers. © 2014 American Society of Plant Biologists. All rights reserved.
CRIS-Team Scopus Importer:2021-07-01

The plant microtubule-associated protein AtMAP65-3/PLE is essential for cytokinetic phragmoplast function - Müller, Sabine; Smertenko, Andrei; Wagner, Vera; Heinrich, Maria; Hussey, Patrick J.; Hauser, Marie-Theres (Current Biology, 2004)
Directional cell expansion in interphase and nuclear and cell division in M-phase are mediated by four microtubule arrays, three of which are unique to plants: the interphase array, the preprophase band, and the phragmoplast. The plant microtubule-associated protein MAP65 has been identified as a key structural component in these arrays [1]. The Arabidopsis genome has nine MAP65 genes, and here we show that one, AtMAP65-3/PLE, locates only to the mitotic arrays and is essential for cytokinesis. The Arabidopsis pleiade (ple) alleles are single recessive mutations, and we show that these mutations are in the AtMAP65-3 gene. Moreover, these mutations cause C-terminal truncations that abolish microtubule binding. In the ple mutants the anaphase spindle is normal, and the cytokinetic phragmoplast can form but is distorted; not only is it wider, but the midline, the region where oppositely oriented microtubules overlap, is unusually expanded. Here we present data that demonstrate an essential role for AtMAP65-3/PLE in cytokinesis in plant cells.
Created from Fastlane, Scopus look-up

The role of the cytoskeleton and associated proteins in determination of the plant cell division plane - Rasmussen, Carolyn G.; Wright, Amanda J.; Müller, Sabine (Plant Journal, 2013)
In plants, as in all eukaryotic organisms, microtubule- and actin-filament based structures play fundamental roles during cell division. In addition to the mitotic spindle, plant cells have evolved a unique cytoskeletal structure that designates a specific division plane before the onset of mitosis via formation of a cortical band of microtubules and actin filaments called the preprophase band. During cytokinesis, a second plant-specific microtubule and actin filament structure called the phragmoplast directs vesicles to create the new cell wall. In response to intrinsic and extrinsic cues, many plant cells form a preprophase band in G2, then the preprophase band recruits specific proteins to populate the cortical division site prior to disassembly of the preprophase band in prometaphase. These proteins are thought to act as a spatial reminder that actively guides the phragmoplast towards the cortical division site during cytokinesis. A number of proteins involved in determination and maintenance of the plane of cell division have been identified. Our current understanding of the molecular interactions of these proteins and their regulation of microtubules is incomplete, but advanced imaging techniques and computer simulations have validated some early concepts of division site determination. © 2013 The Authors The Plant Journal © 2013 John Wiley & Sons Ltd.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Arabidopsis thaliana; cytokinesis; cytoskeleton; division plane; maize; phragmoplast; Physcomitrella patens; preprophase band; Tradescantia virginiana

Transcriptional repression by MYB3R proteins regulates plant organ growth - Kobayashi, Kosuke; Suzuki, Toshiya; Iwata, Eriko; Nakamichi, Norihito; Suzuki, Takamasa; Chen, Poyu; Ohtani, Misato; Ishida, Takashi; Hosoya, Hanako; Müller, Sabine; Leviczky, Tuende; Pettko-Szandtner, Aladar; et al. (EMBO Journal, 2015)
In multicellular organisms, temporal and spatial regulation of cell proliferation is central for generating organs with defined sizes and morphologies. For establishing and maintaining the post-mitotic quiescent state during cell differentiation, it is important to repress genes with mitotic functions. We found that three of the Arabidopsis MYB3R transcription factors synergistically maintain G2/M-specific genes repressed in post-mitotic cells and restrict the time window of mitotic gene expression in proliferating cells. The combined mutants of the three repressor-type MYB3R genes displayed long roots, enlarged leaves, embryos, and seeds. Genome-wide chromatin immunoprecipitation revealed that MYB3R3 binds to the promoters of G2/M-specific genes and to E2F target genes. MYB3R3 associates with the repressor-type E2F, E2FC, and the RETINOBLASTOMA RELATED proteins. In contrast, the activator MYB3R4 was in complex with E2FB in proliferating cells. With mass spectrometry and pairwise interaction assays, we identified some of the other conserved components of the multiprotein complexes, known as DREAM/dREAM in human and flies. In plants, these repressor complexes are important for periodic expression during cell cycle and to establish a post-mitotic quiescent state determining organ size.
CRIS-Team Scopus Importer:2021-07-01
Keywords: cell cycle regulation; cell differentiation; DREAM complex; G2/M phase; MYB transcription factors

Two Kinesins Are Involved in the Spatial Control of Cytokinesis in Arabidopsis thaliana - Müller, Sabine; Han, Shengcheng; Smith, Laurie G. (Current Biology, 2006)
In plant cells, the plane of division is anticipated at the onset of mitosis by the presence of a preprophase band (PPB) of microtubules and F-actin at a cortical site that circumscribes the nucleus. During cytokinesis, the microtubule- and F-actin-based phragmoplast facilitates construction of a new cell wall and is guided to the forecast division site. Proper execution of this process is essential for establishing the cellular framework of plant tissues. The microtubule binding protein TANGLED1 (TAN1) of maize is a key player in the determination of division planes [1-3]. Lack of TAN1 leads to misguided phragmoplasts and mispositioned cell walls in maize. In a yeast two-hybrid screen for TAN1-interacting proteins, a pair of related kinesins was identified that shares significant sequence homology with two kinesin-12 genes in Arabidopsis thaliana (A. thaliana): PHRAGMOPLAST ORIENTING KINESIN 1 and 2 (POK1, POK2). POK1 and POK2 are expressed in tissues enriched for dividing cells. The phenotype of pok1;pok2 double mutants strongly resembles that of maize tan1 mutants, characterized by misoriented mitotic cytoskeletal arrays and misplaced cell walls. We propose that POK1 and POK2 participate in the spatial control of cytokinesis, perhaps via an interaction with the A. thaliana TAN1 homolog, ATN. © 2006 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: CELLBIO

Two new loci, PLEIADE and HYADE, implicate organ-specific regulation of cytokinesis in Arabidopsis - Müller, Sabine; Fuchs, Esther; Ovecka, Miroslav; Wysocka-Diller, Joanna; Benfey, Philip N.; Hauser, Marie-Theres (Plant Physiology, 2002)
In screens for regulators of root morphogenesis in Arabidopsis we isolated six new recessive mutants with irregular cell expansion. Complementation analyses placed the mutations in two loci, PLEIADE (PLE) and HYADE (HYA). Phenotypic analyses revealed multinucleated cells, cell wall stubs, and synchronized cell divisions in incompletely separated cells that are all characteristics of defective cytokinesis. These defects were pronounced in roots and undetectable in aerial organs. In addition, fertility and germination were not affected by the mutations. Thus, the alleles that we have isolated of PLE and HYA suggest that the genes may encode organ-specific components needed primarily during root development. Analysis of microtubule arrays during cell cycle in ple and hya roots indicates that the presence of several synchronized nuclei influences the position of preprophase band, mitotic spindles, and phragmoplasts. The enhanced and synergistic phenotype of PLE/ple.hya/hya seedlings and double mutants point to a role of PLE and HYA in the same process. These mutants provide tools to elucidate the regulation of nuclear cytoskeletal interactions during cell division and cytokinesis.
Created from Fastlane, Scopus look-up

Universal rules for division plane selection in plants - Müller, Sabine (Protoplasma, 2012)
Coordinated cell divisions and cell expansion are the key processes that command growth in all organisms. The orientation of cell divisions and the direction of cell expansion are critical for normal development. Symmetric divisions contribute to proliferation and growth, while asymmetric divisions initiate pattern formation and differentiation. In plants these processes are of particular importance since their cells are encased in cellulosic walls that determine their shape and lock their position within tissues and organs. Several recent studies have analyzed the relationship between cell shape and patterns of symmetric cell division in diverse organisms and employed biophysical and mathematical considerations to develop computer simulations that have allowed accurate prediction of cell division patterns. From these studies, a picture emerges that diverse biological systems follow simple universal rules of geometry to select their division planes and that the microtubule cytoskeleton takes a major part in sensing the geometric information and translates this information into a specific division outcome. In plant cells, the division plane is selected before mitosis, and spatial information of the division plane is preserved throughout division by the presence of reference molecules at a distinct region of the plasma membrane, the cortical division zone. The recruitment of these division zone markers occurs multiple times by several mechanisms, suggesting that the cortical division zone is a highly dynamic region. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Actin filaments; Cell division; Cell shape; Cytoskeleton; Division plane orientation; Microtubules; Phragmoplast; Preprophase band

Update on plant cytokinesis: rule and divide - Buschmann, Henrik; Müller, Sabine (Current Opinion in Plant Biology, 2019)
Many decisions made during plant development depend on the placement of the cytokinetic wall. Cytokinesis involves the biogenesis of the cell plate that progresses centrifugally and until the fusion of the cell plate with the parental cell wall. The phragmoplast facilitates the growth of the cell plate and directs it's insertion at the cell cortex by a mechanism known as phragmoplast guidance. Communication between the phragmoplast and its destination, the cortical division zone, however, is not well understood. The preprophase band predicts the site of cell plate fusion, seemingly controlling the site of the cortical division zone establishment, but recent results suggest the role of this cytoskeletal array to be rather subtle. This is indirectly supported by certain types of phragmoplast-driven cell division in mosses and algae, which lack preprophase bands. In this review article, we summarize recent insight concerning phragmoplast expansion and guidance.
CRIS-Team Scopus Importer:2021-07-01

Update: on selected ROP cell polarity mechanisms in plant cell morphogenesis - Müller, Sabine (Plant Physiology, 2023)
The unequal (asymmetric) distribution of cell structures and proteins within a cell is designated as cell polarity. Cell polarity is a crucial prerequisite for morphogenetic processes such as oriented cell division and directed cell expansion. Rho-related GTPase from plants (ROPs) are required for cellular morphogenesis through the reorganization of the cytoskeleton and vesicle transport in various tissues. Here, I review recent advances in ROP-dependent tip growth, vesicle transport, and tip architecture. I report on the regulatory mechanisms of ROP upstream regulators found in different cell types. It appears that these regulators assemble in nanodomains with specific lipid compositions and recruit ROPs for activation in a stimulus-dependent manner. Current models link mechanosensing/mechanotransduction to ROP polarity signaling involved in feedback mechanisms via the cytoskeleton. Finally, I discuss ROP signaling components that are upregulated by tissue-specific transcription factors and exhibit specific localization patterns during cell division, clearly suggesting ROP signaling in division plane alignment.
CRIS-Team WoS Importer:2023-06-02